The Effect of Teaching Critical Reading Strategies on Kurdish EFL Learners' Reading Comprehension - Faiq, Aseel Muhammad; Muhealddin, Bekhal Latif (Sulaimani Journal for Humanities, 2019)
Reading is an interactive meaning building process that involves numerous activities. In the academic context, it is doubtful whether all EFL learners are aware of the reading strategies. Moreover, even if some learners are aware of these strategies, it is assumed that they may be ill- equipped to handle the academic reading demands. The current paper aims at examining whether Kurdish EFL learners' awareness of the critical reading strategies improve their text comprehension. Fifty students from the College of Languages/ Sulaimani University have been chosen as the sample of the study. These students have been submitted to pre- and post-tests to check the kind of progress they may make after being acquainted with the main ways and methods that can render them good critical readers. The results illustrated a great improvement in the learners' performance as they achieved a comparison rate of 44% (between the pre-and post-tests) mainly in the social task that reflects students' own critical performance. The paper, then, recommends that teaching critical reading strategies to university students should be one of the basic tasks among teachers' teaching activities.
Keywords: Critical readers; critical reading strategies; reading comprehension; critical discourse analysis